Gaps between foresight and policy: The US "Global Trends Report" series case study. (March 2021) - Schmertzing, Leopold
Highlights: Institutional and conceptual gaps hamper the transfer of foresight to policy. Historical and political relevancy and timing decide if foresight passes to policy. Politicians want relevant analysis and do not care for the label foresight. Abstract: This article tries to answer two sets of interlinked questions regarding the Global Trends Report (GTR) series, a successful and well-known example of security policy government foresight: Where and what are the gaps in the transfer of its insight to the policy realm, and who has a good chance of being influenced by its insight and why. The insight produced by the GTR reached its final consumers – the US president, the National Security Council (NSC) and Congress – via two important nodes, political appointees and policy planning units. Other pathways were via the military to Congress and via the media or foreign actors to all final consumers. There is also a good direct connection between GTR and the NSC. History, political decision-making and the presidential term acted as powerful bridges, linking GTR to consumers under certain conditions. GTR had to be in the right historical era to get the attention of anyone beyond its producers. It had to have political relevance for decision makers to get to all final consumers, policy planning units and political appointees. Finally, it had to arrive at the right time, in this case the beginning of the presidential term, to get to all of the above and the media. On an institutional level, the transfer of GTR foresight insight was impeded by prohibitions set down by intelligence agencies against policy advice and against any analysis of the US, and by the disinterest of the bulk of the State Department. GTR also suffered as a result of more conceptual problems: its low political relevance, the divide between academia and political decision-making, and different views on the relationship between foresight and policy. The research also highlighted that common understandings of central concepts facilitated the transfer, the public as an actor in the security sector was weak, understanding the meaning of time in politics was crucial, and the higher the hierarchical position of the consumer, the less important the formal origin of the information became in relation to its political usefulness.